Mid-term follow-up after surgical treatment of fifth metatarsal base fractures in professional soccer players - Lemos, Luis Paulo Vilela; Baumfeld, Tiago Soares; Macedo, Benjamim Dutra; Nery, Caio Augusto de Souza; Batista, Jorge P.; Baumfeld, Daniel Soares (Scientific Journal of the Foot & Ankle, 2019)
Objective: Fifth metatarsal fractures occur mainly in young athletes, with an estimated incidence of 1.8 per 1,000 people a year. The objective of this study was to evaluate the functional outcome of professional soccer players subjected to surgical treatment of fifth metatarsal base fractures. Methods: A total of 34 soccer players who underwent surgery from July 2001 to June 2016 were evaluated. All participants were evaluated by the American Orthopedic Foot and Ankle Score (AOFAS) and visual analogue scale (VAS) score before and after surgery, with a mean follow-up of 23 months. The need for grafting relative to time to surgery, time to fracture consolidation and Torg classification and graft use relative to return to sport were valuated. Results: There were 10 forwards, 7 offensive midfielders, 6 fullbacks, 5 center midfielders, 3 defenders, 2 goalkeepers and 1 defensive midfielder, with a mean age of 19 years. The mean pre- and postoperative AOFAS was 42 and 99 points whereas the mean VAS score was 6 and 0, respectively. The longer the time to surgery, the greater was the need for grafting (p=0.011). The time to return to sport was not influenced by the time to surgery, time to consolidation, Torg classification or graft use. Conclusion: The surgical treatment of fifth metatarsal base fractures in professional soccer players showed good clinical results. The return to activities after surgery is not influenced by the time to surgery, time to consolidation, Torg classification or grafting. Level of Evidence IV; Therapeutic Studies; Case Series.